The Role of Higher Education and Artificial Intelligence in Improving 4C Competencies in the Revolution 5.0 Era - Asyifa, Eteh Resa; Rohida, Leni (Cirebon Annual Multidiciplinary International Conference (CAMIC), 2025)
This research explores the important role of higher education and artificial intelligence in developing 4C competencies, i.e. Communication, Collaboration, Critical Thinking, and Creative Thinking. In the midst of the Industrial Revolution 5.0, 4C skills are key to preparing graduates who are able to compete in the job market. Higher education holds the responsibility to develop these skills through innovative curriculum and problem-based learning approaches. This research uses a qualitative descriptive method. The results revealed that higher education plays an important role in preparing students with the 4C skills that are needed in the 21st century. By integrating artificial intelligence into the learning process, higher education can create a more dynamic and interactive learning environment. This approach not only improves students' communication and collaboration skills, but also encourages them to think critically and creatively in the face of diverse global challenges. Therefore, curriculum reform and the application of innovative teaching methods are necessary to achieve this goal.